PENGARUH LATAR BELAKANG PENDIDIKAN ORANG TUA TERHADAP PENGETAHUAN AGAMA DAN KARAKTER RELIGIUS SISWA DI MADRASAH IBTIDAIYAH SHIRROTUL JANNAH PALEMBANG - Muhammad Abduh; Fajri Ismail; Muhammad Win Afgani (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Abstract Education is important for human survival, and for the progress of the nation. Education is an effort to rise for equity and increase the potential of students to achieve the desired quality of education. Character is the most important aspect in creating quality human resources, national character determines the progress of a nation. Quality character needs to be formed and nurtured from an early age. religious character refers to asmaul husna so that it becomes an inspiration in everyday life, such as being able to emulate the nature of God who is responsible, fair, honest, visionary, caring, and so on. religious students. The practical benefits of this research can be input and suggestions for educators and parents as a solution in solving the problem of religious character and religious knowledge of students in schools. The method used is a quantitative research method by collecting data by distributing questionnaires. Students' religious knowledge is still low and students' religious character is still far from expectations.